MRI Protocol 2017_110 TMS Plasticity 3 - Lazari, A (University of Oxford, 2021)
This file is an MRI acquisition protocol. It consists of a battery of microstructural scans (Multi-shell Diffusion-Weighted Imaging, and Multi-Parameter Mapping), tailored to quantify myelination changes in healthy young adults as part of a longitudinal experimental design. It also includes resting-state fMRI and a large-FOV T1w structural scan that can be used to target non-invasive brain stimulation.